2019
DOI: 10.1016/j.gaitpost.2018.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the stabilometer balance test: Bridging the gap between clinical and research based balance control assessments for stroke patients

Abstract: Background: A pronounced discrepancy exists between balance assessments for stroke survivors that are used for clinical purposes and those used for research. Clinical assessments like the Berg Balance Scale generally have stronger ecological validity, whereas research-based assessments like posturography are generally more reliable and precise. We developed a stabilometer balance test (SBT) that aims to couple measurement reliability and precision to clinical meaningfulness by means of a personalized and adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…In the present study, learning and motor performance were reported as the amount of time needed to maintain dynamic balance in the elderly. The stabilometer was used to measure dynamic balance [21]. This device includes a moving plate (platform), a chassis and a control unit.…”
Section: Apparatus and Taskmentioning
confidence: 99%
“…In the present study, learning and motor performance were reported as the amount of time needed to maintain dynamic balance in the elderly. The stabilometer was used to measure dynamic balance [21]. This device includes a moving plate (platform), a chassis and a control unit.…”
Section: Apparatus and Taskmentioning
confidence: 99%
“…A custom-made, validated balance board task 32 was used to test patients' balance performance, and also for the interventions ( Figure S1). This balance board task taxes mediolateral balance control, which is often impaired after stroke.…”
Section: Materials and Measuresmentioning
confidence: 99%
“…With this procedure, task difficulty is adjusted on a trial-to-trial basis, based on prespecified criteria. Please see Brouwer et al 32 for the full-test protocol. Patients only received unfocused instructions ("stand as still as possible").…”
Section: Materials and Measuresmentioning
confidence: 99%
See 2 more Smart Citations